The D1/D2-like receptor antagonist flupentixol and the D2-like receptor antagonist L-741626 decrease operant responding for nicotine and food and locomotor activity in male and female rats. (February 2023) - Chellian, Ranjithkumar; Behnood-Rod, Azin; Wilson, Ryann; Lin, Karen; Wing-Yan King, Grace; Bruijnzeel, Adriaan W
Background: The reinforcing properties of nicotine play a critical role in smoking and vaping. There is a need for treatments that decrease the reinforcing properties of nicotine and thereby improve smoking and vaping rates. Dopamine plays a role in the reinforcing properties of nicotine, but little is known about the role of dopamine D2-like receptors in nicotine intake and whether there are sex differences in the effects of dopaminergic drugs on nicotine intake. Aim: The goal of the present studies was to investigate the effects of the D1/D2-like receptor antagonist flupentixol and the D2-like receptor antagonist L-741626 on nicotine self-administration in male and female rats. Methods: The effects of flupentixol and L-741626 on operant responding for nicotine and food and locomotor activity in a small open field were investigated. Results: There were no sex differences in baseline nicotine intake. The D1/D2-like receptor antagonist flupentixol and the D2-like receptor antagonist L-741626 decreased operant responding for nicotine. Blockade of D1/D2-like receptors and blockade of D2-like receptors also decreased operant responding for food and decreased locomotor activity. Flupentixol induced a greater decrease in operant responding for food in males than females. However, in the other tests, there were no sex differences in the effects of the dopamine receptor antagonists. Conclusions: Blockade of D1/D2-like receptors with flupentixol and D2-like receptors with L-741626 decreases nicotine and food intake in rats of both sexes. These compounds also decrease locomotor activity which might be indicative of a sedative effect.